PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DEBT TO EQUITY RATIO, CURRENT RATIO, dan TOTAL ASSETS TURNOVER TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2017) - Niken Rahma Putri, 15.05.52.0056; Aini, Nur (Students' Journal of Accounting and Banking, 2019)
This study aims to examines the effects of Return On Return, Earning per Share, Debt to Equity Ratio, Current Ratio, and Total Assets Turnover on stock prices. This research was conducted on pharmaceutical sub-sector companies that listed on the Imdonesian Stock Exchange. The sampling method that used in the study was purposive sampling with a total sample of observation of 7 companies and the number of observation data many as 70 in the period 2008-2017. The data analysis technique used in this study is Fixxed Effect Least Square Dummy Variabel (LSDV). The result showed that the Return On Equity and Debt to Equity Ratio has a positive effect but not significant on stock prices. Earning per Share and Total Assets Turnover has a negative affect but not significant on stock prices. Current Ratio has a negative and significant effect on stock prices.